If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x = 6x + 2 Reorder the terms: 7x = 2 + 6x Solving 7x = 2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 7x + -6x = 2 + 6x + -6x Combine like terms: 7x + -6x = 1x 1x = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 1x = 2 + 0 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| 14=-4x^2+12x+14 | | 0.20(18)+0.05x=0.10(6+x) | | 28=x^2+9x+18 | | 4=x^2+9x+18 | | 3x+(-3y)-(4x)+y= | | 172-4x=23x+16 | | 2x^6w^4*2w^3*4x= | | 6=x^2-7x+12 | | 2=x^2-7x+12 | | 2x^2-x=120 | | 1.25x+0.125x=0.875+x | | 3x^2+9x=54 | | -16x^2+220x=0 | | 7+2x*5=x*6+11 | | -8x^3-20x^2=8x | | (5x+4)(3x-3)=0 | | x-8=4x | | 9x^2=51x-60 | | 6(t-5)+8t=7(2t+4)-11 | | 5t+2+4t-8t=5+5 | | 4(x-3)=-(x+7) | | (x-5)(x+3)(x+4)=0 | | x-(x+1)=12-(3x-2) | | y=x^2-x-23 | | 4(9v+2)=6(1+6v)-10 | | 2x=x+65 | | -2(c-d)+(c-3d)-5(c-d)= | | -0.5x^2+2x-70=0 | | 6a+4=a+7 | | -20x^2-8x+64=0 | | 2n^2+33n-17=0 | | 2.5x+0.25x=0.75+x |